Timber Harvest Impacts on Water Yield in the Continental/Maritime Hydroclimatic Region of the United States - Jason A. Hubbart; Timothy E. Link; John A. Gravelle; William J. Elliot (Forest Science, 2007)
The inland Pacific Northwest of the United States is influenced by both maritime and continental hydrometeorogical conditions. To date there are limited studies of hydrologic impacts resulting from contemporary timber harvest in this region. Streamflow data were collected since 1991 at the Mica Creek Experimental Watershed (MCEW) in northern Idaho. Treatments were designed to isolate the effects of road construction and two different harvest practices (50% clearcut, 50% partial cut). The change in water yield was assessed using linear regression and analysis of covariance (ANCOVA). Water yield increased in excess of 270 mm/yr (P < 0.01) after clearcut harvesting, and by more than 140 mm/yr (P < 0.01) after partial cut harvesting. Monthly and seasonal analyses revealed the largest impacts of harvest practices on water yield during the snow deposition and melt season from November through June. Dry season analyses (July through October) indicated negligible water yield increases after treatments. Estimates of evapotranspiration (ET) as the residual of the catchment water balance suggest that ET was reduced by 35% and 14% after clearcut and partial cut harvest, respectively. These results establish a base on which to develop tools for effective watershed management in the northern Idaho continental/maritime hydroclimatic region.